A Survey of Mongols and Their Successors Beliefs in Persian Context - Alavijeh, Ali Zamani (ASPENSI in Bandung, Indonesia, 2013)
ABSTRACT: What distinguishes the Old Mongols is their devotion to and love of Nature, the far-reaching scope of their spiritual awareness, unending mental curiosity and nearly limitless endurance, and quest for excellence in every endeavor. Since Genghis Khan is the founder of the Mongol nation, we use his name as a starting point, and see where we get if we try to compare the qualities of water with those of the Genghis-Khanite Mongols. Afterwards, we shall look more closely on their thoughts and beliefs. Hence, the Mongolian taboos, rules of restrictions, and unwritten law are traditions inherited not only from our ancestors, but also from the teachings of Genghis Khan, contained in the Code of Law of Great Mongolia called